PEMBANGUNAN SISTEM INFORMASI ADMINISTRASI DESA BERBASIS WEB DENGAN MENGGUNAKAN FRAMEWORK LARAVEL - Andrew Robot Feldy Najoan; Nina Setiyawati (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Sonder District, especially the village of Kolongan Atas II. Still processing data and information using conventional methods, namely village information only through loudspeakers or RT/RW meetings. In addition to the ity of service to the community, it still cannot be maximized because it still uses the manual method to make village administration, therefore a village administration information system was created to support and facilitate administration in the village of Kolongan Atas II. The method that will be used in making the website uses the waterfall model. This research will also produce a web-based village administrative information system that can facilitate information search and administration in Kolongan Atas II village. As well as being able to explore the potential of village data and information about the village.